2005
DOI: 10.1016/j.ijid.2004.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses induced by Mycobacterium tuberculosis in patients with HIV-1 infection and tuberculosis

Abstract: Cytokine responses to M. tuberculosis were retained in HIV-infected patients with tuberculosis, even in patients with a CD4 cell count of less than 200/mm3, and reconstituted after HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
4
1
Order By: Relevance
“…Despite an extensive literature that suggests that IFN-γ responses to mycobacterial antigens are decreased but detectable in HIV-infected individuals [8,10,14,26,27], we did not see differences in IFN-γ responses in subjects with and without TB. One reason for this discrepancy may be differential assay duration.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite an extensive literature that suggests that IFN-γ responses to mycobacterial antigens are decreased but detectable in HIV-infected individuals [8,10,14,26,27], we did not see differences in IFN-γ responses in subjects with and without TB. One reason for this discrepancy may be differential assay duration.…”
Section: Discussioncontrasting
confidence: 99%
“…Another potential reason for the discrepant IFN-γ results in this study is that certain mycobacterial antigens may be more efficient at generating IFN-γ responses than others. Commercially available assays of IFN-γ target ESAT-6 as well as CFP-10 with and without TB7.7 [4,25], and others have demonstrated detectable IFN-γ responses in HIV-infected subjects with active TB using purified protein derivative (PPD) [8,14] Our assay, which assessed responses to ESAT-6, Ag85 and WCL, may be less likely to generate IFN-γ responses that distinguish between subjects with and without TB. At a minimum, our data suggest that incubation period and antigen choice are critical variables in IFN-γ assays for TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that specific T cell responses in TB patients with advanced immunosuppression are impaired [12]. However, this is not supported by several other studies [13,14,15]. Blood-based IFN-γ assays are fast becoming the standard for diagnosing latent TB and are now performed in an increasing number of laboratories worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In HIV infection, IFN-g plays a vital role in the reduction of HIV replication. It was shown that the progression of immunodeficiency was associated with diminished IFN-g production [40,41]. Also, IFN-g has a major role in protecting against TB [38,42,43].…”
Section: Introductionmentioning
confidence: 99%